Effect of different diets on growth performance of Muscovy Duck by using rice bran as a basal diet - NAOYENG, Khamkeo; PHONEYAPHON , Vanhnasin; BOUNTAVY, Davan (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The objective of experiment was study on effect of different diets on growth performance of Muscovy Duck by using rice bran as a basal diet, feed intake, feed conversion ratio and economic return. The experiment was conducted at: Experimental center of the office of Agriculture and Forestry, Aat District in center location, Houaphan Province. The duration of experiment were 63 days, for the feed offer was fed adlibitum, four treatments were compared in a RCBD with four replications of four treatments: T1 = Concentrate feed 60% + Rice bran 40%, T2 = Concentrate feed 50% + Rice bran 40% + Maize 10%, T3 = Concentrate feed 50% + Rice bran 40%+ water spispinach 10%, T4= Concentrate feed 55% + Rice bran 40% + Earthworm 5% ; The animal house were newly built which 16 cages made from local materials (Bamboo) and the roof is covered by Imperata cylindrical. In each cages has a water and feed trough and in one cages have three ducks (width 75 cm and length 90 cm) and the house width 3 m and length 5m. the duck were feed two time per day at: 7:00 Am and 14:30 PM. Feed offer and feed residue were collected every day and the animal were weight every one week (7 days). The resulted of experiment were shown: Feed intake per day was high in T4: 188.8 g/head/day and lowest in T3 = 155.7 g/head/day and there were different (P<0.05). The Average daily gain (ADG) was high in T4 = 45.24 g/head/day, and lowest in T3 = 38.56 g/head/day and they were different among treatment (P<0.05). However, feed conversion ratio (FCR) of each treatment not different as: T1 = 4.1; T2= 4.2; T3 = 4.17 and T4= 4.0 respectively and there were non-significant (P>0.05). Economic return was shown: T1 = 59,210 Kip/head, T2 = 53,471 head, T4 = 51,950 head and T3 = 50,880 head.